Opportunities and Challenges of Islamic Republic of Iran’s Accession to the Vienna Convention on Civil Liability for Nuclear Damage - A Shamshiri; F Amirabadi Farahani (مجله علوم و فنون هسته‌ای, 2018)
Nowadays the Islamic Republic of Iran is known as a nuclear state and It’s nuclear activities are increasing every day. However it has not been thought about liability for potential hazards of these damages. Leading nuclear countries, in addition to developing a civil liability law on nuclear activities, have become parties to the relevant conventions. These conventions including the Vienna Convention are based on the basic principles governing civil responsibility for nuclear events. The benefits of membership in the convention are: channeling of liability to operator, limitation of liability in amount and time, operator’s absolute liability and … that they contribute to the development of the nuclear industry. In some cases, the compensation is referred to domestic la which despite its benefits for avoiding inconsistencies in the legal system of countries in solving specific problems, In our country, because of the lack of specific civil nuclear legislation, it is actually a challenge. Therefore legislation in this field is more necessary.